THE INFLUENCES OF GREEN INNOVATION ON GREEN ORGANIZATIONAL PERFORMANCE – CONCEPTUAL OVERVIEW (Journal of Technology and Operations Management, 2017)
As the increase of awareness on human health and environment, consumers are now looking for Green products compliance (especially electrical and electronic equipment). This has creates more demand on Green products which has led an organization to invest on innovation. However, the successful of the innovation activities will be dependent on how the organization manage the internal factors (readiness on its process capabilities, resources, supply chain and etc.) and also external forces (environmental regulations, customer requirements, etc.) – Green Management. This paper is aiming at the linkage of these relationship: Green management, Green innovation and Organizational performance. The study will be conducted to the electrical and electronic supply chain firms in Malaysia; which are globally known as electrical and electronic manufacturing hub in the world. Researchers believe that the findings from this study will soon bring benefits to the practitioners and academia. As the practitioners (specifically refers to the electrical and electronic organizations) the study will help them to understand on how the influences of Green innovation can affect Green organizational performance. While for academia, this study is believed to explore another areas of Green innovation which previously many past studies concentrated only on definitional issues and theoretical explanation.